2018
DOI: 10.1111/aogs.13352
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy for idiopathic recurrent pregnancy loss – a systematic review and meta‐analyses

Abstract: The literature does not allow advice on any specific treatment for idiopathic recurrent pregnancy loss, with the exception of progesterone starting from ovulation. We suggest that any treatment for recurrent pregnancy loss should be used within the context of a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 70 publications
2
32
0
3
Order By: Relevance
“…Additional proposed etiologies include inherited thrombophilia, luteal phase defect, immunologic abnormalities, and sperm DNA fragmentation. Up to half of RPL cases are unexplained (23)(24)(25).…”
Section: Treating Rheumatologic Aspects Of Recurrent Pregnancy Lossmentioning
confidence: 99%
“…Additional proposed etiologies include inherited thrombophilia, luteal phase defect, immunologic abnormalities, and sperm DNA fragmentation. Up to half of RPL cases are unexplained (23)(24)(25).…”
Section: Treating Rheumatologic Aspects Of Recurrent Pregnancy Lossmentioning
confidence: 99%
“…Glucocorticoid treatment has produced inconsistent results in RM patients and can increase the risk of prematurity, orofacial clefts, gestational diabetes and hypertension . A recent meta‐analysis using strict criteria for defining unexplained RM found no RCTs involving prednisolone . Two recent meta‐analyses of intravenous immunoglobulin (IVIg) use in RM found no evidence of improved live birth rates .…”
Section: Immunological Factors and Progesterone Supplementationmentioning
confidence: 99%
“…A recent meta‐analysis using strict criteria for defining unexplained RM found no RCTs involving prednisolone . Two recent meta‐analyses of intravenous immunoglobulin (IVIg) use in RM found no evidence of improved live birth rates . Recent meta‐analyses of allogenic lymphocyte immunotherapy (eg paternal lymphocyte infusion) reported improved live birth rates in the treatment arm .…”
Section: Immunological Factors and Progesterone Supplementationmentioning
confidence: 99%
“…It has been argued that ASA prevents placental thromboses . We conducted a systematic search in the Cochrane Library, PubMed and Embase for studies that reported on treatments with ASA for RPL . In couples with at least 3 consecutive miscarriages, ASA is sparsely investigated in randomized clinical trials (RCT) and has mostly been included together with other drugs .…”
Section: Introductionmentioning
confidence: 99%
“…20 We conducted a systematic search in the Cochrane Library, PubMed and Embase for studies that reported on treatments with ASA for RPL. 21 In couples with at least 3 consecutive miscarriages, ASA is sparsely investigated in randomized clinical trials (RCT) and has mostly been included together with other drugs. 11,22 Only 1 small RCT including 54 patients has compared 50 mg ASA with placebo, resulting in the same live birth rate of 81%.…”
mentioning
confidence: 99%